Fundamental contributions of neuroscience to motor learning in children: a systematic review - María-José; Esteban Aedo-Muñoz; Cristian Hernández-Wimmer; Ciro José Brito; Bianca Miarka (Desafio Singular, 2022)
Motor learning generates synaptic neural connections that favour the motor environment and, also, various processes where our cognitive and executive functions intervene. Therefore, it is essential to know the different contributions that come from neuroscience linked to motor learning in a child. This study aimed to determine the fundamental contributions of neuroscience to motor learning in children. The methodology included a qualitative systematic review in the PubMed, Medline and Scopus databases. Of 479 related documents, 24 papers achieved the inclusion criteria (the learning mechanisms of motor skills and the different approaches to achieving meaningful learning). They were selected using the data collection methodology indicated by PRISMA®. The main results indicated that learning occurs based on experiences (cognitive, perceptual, motor, linguistic, neuronal, organic and cultural) and requires processes of adaptation, stabilization, and maturation of brain synchronization of vestibular, perceptual and visual processes. Children who receive motor intervention improve sustained attention, working memory, problem-solving and planning capacity. Motor and cognitive development are favoured by instructions as an essential tool. The implicit instructions present a higher benefit for children with lower motor skills.